Clinical outcome of transfusions with extended red blood cell matching in β-thalassemia patients: A single-center experience. (February 2019) - Belsito, A.; Costa, D.; Signoriello, S.; Fiorito, C.; Tartaglione, I.; Casale, M.; Perrotta, S.; Magnussen, K.; Napoli, C.
Abstract: Background: The development of alloantibodies may complicate the management of patients with β-thalassemia. An extended antigenic matching may reduce the risk of alloimmunization. Our previous study showed that the introduction of molecular red blood cell (RBC) typing allows finding suitable blood units for multi-transfused patients. The aim of this study was to evaluate the benefit of RBC transfusion with extended antigenic match. Materials and methods: At the University of Campania "L. Vanvitelli", we selected β-thalassemia major patients (age ≤23 years), without preformed alloantibodies. Data of patients receiving transfusion of leukoreduced RBC units for a period of one year with partial better match (PBM) including ABO, RhD, C/c, E/e, K/k antigens and consecutive one year with extended match (EM) including ABO, RhD, C/c, E/e, K/k, Fy a /Fy b, Jk a /Jk b, M/N, S/s antigens, were compared. Results: Eighteen patients, 8 males and 10 females with a mean age of 15.4 years (6.4 SD) received a mean number of 41.2 (6.0 SD) RBC units transfused with PBM and 41.8 (6.2 SD) with EM protocols. After two years of RBC transfusions with both antigen matching protocols, no new alloantibodies were developed in patients. No significant differences in Hb concentration and volume of RBC transfused were found between PBM and EM protocols. Conclusions: Thalassemia patients may benefit from receiving RBC transfusions based on extended antigen matching as demonstrated by the lack of new alloantibodies. However, our data show a high concordance between PBM and EM protocols considering pre-transfusion Hb, increment of Hb and volume of RBC transfused.